THE IMPORTANCE OF MANAGEMENT PROCESSES IN CLEANER PRODUCTION RESULTS: A STUDY IN THE PLASTIC INDUSTRY - Buccelli, Dalton Oswaldo; Costa Neto, Pedro Luiz de Oliveira (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The paper reports a study on the implementation of cleaner production in the plastic industry. The study aimed to develop a model for assessingthe quality of environmental management to prove the proposition that permanent cleaner production outcome has a positive relationshipwith the existence of structured and standardized management processes in the company. A literature review allowed the development ofa model to evaluate the degree of structuring and standardization of management processes, using as reference the existing literature onbusiness models and process management, as well as excellence models adopted by national quality awards from different countries andcontinents. The proposition of a positive relationship between the structured management processes and environmental performance of thecompanies was confirmed by quantitative survey with 32 companies’ members of the São Paulo plastic industry association - SINDIPLAST.These findings on significant environmental results from the incorporation of principles and concepts of cleaner production in managementprocesses will allow to do further studies in other locations and other industry sectors.